N-[3-(Dimethylamino)propyl]-N,N′,N′,N′′,N′′-pentamethylguanidinium tetraphenylborate - Tiritiris, Ioannis (International Union of Crystallography, 2013)
In the title salt, C(11)H(27)N(4) (+)·C(24)H(20)B(−), the C—N bond lengths in the central CN(3) unit of the guanidinium ion are 1.333 (4), 1.334 (4) and 1.351 (4) Å, indicating partial double-bond character. The C atom of this unit is bonded to the three N atoms in a nearly ideal trigonal-planar geometry [N—C—N angles = 118.8 (3), 120.0 (3) and 121.2 (3)°] and the positive charge is delocalized in the CN(3) plane. The bonds between the N atoms and the terminal C-methyl groups of the guanidinium moiety have values in the range 1.459 (4)–1.478 (4) Å, close to a typical single bond. In the crystal, there are C—H⋯π interactions between the guanidinium H atoms and the phenyl rings of the tetraphenylborate ion. These interactions combine to form a ladder of linked chains of ions which runs parallel to the c axis.